Gambaran Pola Konsumsi Mie Instan Anak Sekolah Dasar pada Keluarga Petani di Wilayah Desa Sumberagung-Jember - Safitri, Rizqi Diana; Juliningrum, Peni Perdani; Sulistyorini, Lantin (Pustaka Kesehatan, 2024)
Giving frequently instant noodles to children will form a habit, making children only want to consume instant noodles. Consuming instant noodles twice or thrice a week increase risk of cardiometabolic syndromes such as heart disease, stroke and diabetes which are the common causes of death worldwide. This study aimed to describe the pattern of instant noodle consumption among elementary school children of farmer families in Sumberagung Village, Jember Regency. The study used a quantitative descriptive design with a sample of 58 elementary school age children grades IV, V, VI who were selected using purposive sampling technique. Data were collected using a Food Frequency Questionnaire (FFQ). The result showed that the consumption pattern of Instant Noodles for elementary school children in farming families was in the category of 3-6x/week, >3x/day, 1x/day, and 1-2x/week were 43.1%, 17.2%, 31%, and 8.6%, respectively. This study concluded that the consumption pattern of instant noodles among elementary school children in farmer families in Sumberagung Village, Jember Regency is in a dangerous risk for health. Therefore, it is expected that health workers improve education on Balanced Nutrition Messages (PGS), so that farmer families, especially mothers can prepare healthy, safe and nutritious meals for children and their families.